Scientific drilling and downhole fluid sampling of a natural CO2 reservoir, Green River, Utah - N. Kampman; A. Maskell; M. J. Bickle; J. P. Evans; M. Schaller; G. Purser; Z. Zhou; J. Gattacceca; E. S. Peitre; C. A. Rochelle; C. J. Ballentine; A. Busch; et al. (Scientific Drilling, 2013)
A scientific borehole, CO2W55, was drilled into an onshore anticline, near the town of Green River, Utah for the purposes of studying a series of natural CO2 reservoirs. The objective of this research project is to recover core and fluids from natural CO2 accumulations in order to study and understand the long-term consequences of exposure of supercritical CO2, CO2-gas and CO2-charged fluids on geological materials. This will improve our ability to predict the security of future geological CO2 storage sites and the behaviour of CO2 during migration through the overburden. The Green River anticline is thought to contain supercritical reservoirs of CO2 in Permian sandstone and Mississippian-Pennsylvanian carbonate and evaporite formations at depths > 800 m. Migration of CO2 and CO2-charged brine from these deep formations, through the damage zone of two major normal faults in the overburden, feeds a stacked series of shallow reservoirs in Jurassic sandstones from 500 m depth to near surface. The drill-hole was spudded into the footwall of the Little Grand Wash normal fault at the apex of the Green River anticline, near the site of Crystal Geyser, a CO2-driven cold water geyser. The hole was drilled using a CS4002 Truck Mounted Core Drill to a total depth of 322 m and DOSECC’s hybrid coring system was used to continuously recover core. CO2-charged fluids were first encountered at ~ 35 m depth, in the basal sandstones of the Entrada Sandstone, which is open to surface, the fluids being effectively sealed by thin siltstone layers within the sandstone unit. The well penetrated a ~ 17 m thick fault zone within the Carmel Formation, the footwall damage zone of which hosted CO2-charged fluids in open fractures. CO2-rich fluids were encountered throughout the thickness of the Navajo Sandstone. The originally red sandstone and siltstone units, where they are in contact with the CO2-charged fluids, have been bleached by dissolution of hematite grain coatings. Fluid samples were collected from the Navajo Sandstone at formation pressures using a positive displacement wireline sampler, and fluid CO2 content and pH were measured at surface using high pressure apparatus. The results from the fluid sampling show that the Navajo Sandstone is being fed by active inflow of CO2-saturated brines through the fault damage zone; that these brines mix with meteoric fluid flowing laterally into the fault zone; and that the downhole fluid sampling whilst drilling successfully captures this dynamic process.